La biografía de Aspasia de Focea en Eliano (Minerva. Revista de Filología Clásica, 2019)
The story of the enigmatic Aspasia of Phocis, briefly related in the Greek literature since Xenophon, is specially developed in Aelian’s Varia Historia. This paper intends to study the new data that Aelian added to Aspasia’s literary biography, among them folk topics such as the presence of number three, healings through unconventional methods, warning dreams, magic transformations of animals into human beings…, which were thought to provide readers, fond of superstition and pseudo-scientific curionsities, with entertainment.